A synopsis of feral Agave and Furcraea (Agavaceae, Asparagaceae s. lat.) in the Canary Islands (Spain) - Filip Verloove; Joachim Thiede; Águedo Marrero Rodríguez; Marcos Salas-Pascual; Jorge Reyes-Betancort; Elizabeth Ojeda-Land; Gideon Smith (Plant Ecology and Evolution, 2019)
Background – Species of Agave and Furcraea (Agavaceae, Asparagaceae s. lat.) are widely cultivated as ornamentals in Mediterranean climates. An increasing number is escaping and naturalising, also in natural habitats in the Canary Islands (Spain). However, a detailed treatment of variously naturalised and invasive species found in the wild in the Canary Islands is not available and, as a result, species identification is often problematic.Methods – The present study is based on many years of fieldwork on the islands of Fuerteventura, Gran Canaria, Lanzarote and Tenerife. Results – Fourteen species and several additional infraspecific taxa of Agave have been identified. In addition to the widely naturalised and invasive Agave americana, A. fourcroydes and A. sisalana (incl. the not previously reported var. armata), the following species of Agave were observed: A. angustifolia (incl. var. marginata), A. attenuata, A. filifera, A. franzosinii, A. lechuguilla, A. macroacantha, A. murpheyi, A. oteroi, A. salmiana (var. ferox and var. salmiana), A. aff. tequilana and A. vivipara. From the genus Furcraea three species were found: F. foetida, F. hexapetala and F. selloana. Several of these newly detected species of Agave and Furcraea are at least locally naturalised. A key for the identification of the representatives of these genera in the study area is presented and all species are illustrated. Additional nomenclatural, taxonomic and ecological notes are also provided.